Nurses’ behavior toward patient safety in Hospitals: A systematic literature review - Ronaldo, Melky Sedeq Norman; Haryanto, Haryanto; Suriadi, Suriadi; Saragih, Septina Boru; Gustaman, Budi (JOURNAL OF Mental Health Concerns, 2026)
Background: Patient safety is a global health priority that is closely related to the quality of nursing care. Nurse behavior is a major determining factor in preventing Patient Safety Incidents (PSIs) in hospitals. Purpose: To identify and analyze factors that influence nurse behavior in implementing patient safety in hospitals. Method: The research design was a Systematic Literature Review (SLR) following the PRISMA guidelines. Articles were searched for in the Wiley Online Library, PubMed, and ScienceDirect databases for publications from 2015 to 2025. From the screening results, 11 articles that met the inclusion criteria were selected. Results: The analysis revealed four main themes that influence nurses' safety behavior: (1) Organizational culture and teamwork; (2) Work environment conditions (night shifts and workload); (3) Psychological factors (stress and burnout); and (4) Effectiveness of interprofessional communication and situational awareness. A strong safety culture was found to increase nurses' courage to speak up (voice behavior), while work stress and physiological fatigue were major barriers to compliance with safety principles. Conclusion: Nurses' patient safety behavior is influenced by the interaction between systemic management support and individual psychological well-being. Improving patient safety requires a comprehensive approach that focuses not only on technical training but also on improving shift management and creating a non-punitive work environment. Keywords: Nurses; Nurse Behavior; Patient Safety.